ANALISIS FAKTOR-FAKTOR PENGARUH MINAT PENGGUNAAN SISTEM INFORMASI AKUNTANSI BERBASIS E-COMMERCE PADA APLIKASI SHOPEE DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Angela Deananda Putri Budiastuti; Dul Muid (Diponegoro Journal of Accounting, 2020)
This study aims to analyze the factors that influence interest in using accounting information system based on e-commerce in Shopee with Technology Acceptance Model (TAM). Data collection is done by giving a questionnaire to respondent as Shopee user in Semarang city. 201 respondents were obtained by purposive sampling method. Data measurement is using multiple regression analysis in SPSS.The results showed that Perceived Ease of Use, Trust, and Attitude Towards Using have positive effect in interest of use, whereas Perceived Usefulness and Risk have no significant effect in interest of use. Interest of using Shopee influenced by ease, trust, and acceptance attitude in using Shopee. Perecived usefulness has no significant influence in interest, whereas the existence of risk in Shopee will inhibiting the interest in using Shopee